Relationship between cumulative exposure to pesticides and sleep disorders among greenhouse vegetable farmers - Jiangping Li; Yanxing Hao; Danian Tian; Shulan He; Xian Sun; Huifang Yang (BMC, 2019)
Abstract Background In the northern region of China, many greenhouse vegetable farmers are exposed to high cumulative levels of pesticides due to long-term work in greenhouses that impacts their health. The aim of the current study was to identify the relationship between cumulative pesticide exposure and sleep disorders among farmers in Yinchuan, Northwest China. Methods A cross-sectional study was conducted for 3 consecutive years in 2015, 2016 and 2017. Using a random sampling to select the resident teams, 1366 participants were enrolled, and information was collected via face-to-face interviews by trained investigators. Ordinal logistic, multinomial logistic and poisson logistic regression models were used to identify the associations between cumulative exposure intensity (CEI) and sleep disorders. Results High CEI (OR = 1.56, 95% CI: 1.02-3.38) was associated with short sleep duration when compared with low CEI in the Full Model. CEI was not associated with long sleep duration. Self-rated sleep quality was associated with medium (OR = 1.46, 95% CI: 1.10-2.00) and high (OR = 2.50, 95% CI: 1.83-3.40) CEI. Similarly, having difficulty sleeping was associated with medium (OR = 1.52, 95% CI: 1.02-2.24) and high (OR = 1.74, 95% CI: 1.16-2.62) CEI. Differences in the associations by gender were also noted. Conclusion CEI was associated with sleep disorders, and gender differences were observed. Efforts should be made by local governments to address sleep problems that result from cumulative pesticide exposure in farmers, and gender differences should be considered.